Implementation Of Gender Equality Education In The Boarding School Tarbiyatul Mu'allimat Al-Islamiyah Al-Amien Prenduan Sumenep - Sutrisno, Andri; Kuswandi, Iwan (IJIBS, 2023)
Education and pesantren are two parts that cannot be separated for the survival of the students. One of the bad stigmas among society is that a woman is marginalized by men, so there are many cases of harassment or even violence against a woman. With the existence of islamic boarding schools in Indonesia, it turns out that it has a change in the order of society to raise the degree of women in Indonesia. That men are now also activists to maintain the existence of a woman. The existence of this islamic boarding school provides a solution to raise the degree of a woman because in pesantren today it has taught several skills and education based on gender equality education. Thus, female students can grow and develop with confidence to defend themselves to be able to compete with a man. In this study, researchers used a qualitative field approach with a type of case study research. While the method in collecting data, researchers use three methods, namely observation, interview and documentation. Meanwhile, the data analysis technique is through data reduction, data exposure and data verification. The form of implementation of gender equality education management applied in tarbiyatul mu'allimat al-islamiyah is leadership and management training, worksop improvement of group leaders and organizational skills among female students while the advantage of this implementation is the confidence of each student to be able to compete with a man and have a trustworthy and honest leadership spirit. Meanwhile, the drawback is that there are some students who are indifferent in carrying out and implementing the discipline of islamic boarding schools that have been mutually agreed upon, both kyai, teachers and students.